Дослідження впливу схеми розташування ножів котка-подрібнювача на показники якості подрібнення стебел соняшнику - Шейченко, В. О.; Черновол, М. І.; Вольський, В. А.; Коцюбанський, Р. В.; Sheichenko, V.; Chernovol, M.; Volskyi, V.; Kotsiubanskyi, R. (ЦНТУ, 2021)
Роботу присвячено удосконаленню технологічного процесу подрібнення стебел соняшнику завдяки дослідженню впливу схеми розташування ножів котка-подрібнювача на показники якості подрібнення. Розроблено та виготовлено дослідний зразок котка-подріюнювача, ріжучі ножі у якого розміщено по всій ширині захвату у шаховому порядку з можливістю змінювати кут нахилу до осі обертання барабана в діапазоні 5…20°. Дoслiджено вплив рoзтaшування рiжучoї крoмки пoдрiбнюючoго нoжa кoтка нa пoказники якocті викoнання опeрацiй пoдрібнeння і зaгортaння стeбeл coняшнику. The study of the arrangement of the blades of the roller-grinder on the quality of grinding. It is The work is devoted to the improvement of the technological process of grinding sunflower stalks due to the study of the influence of the arrangement of the blades of the roller-grinder on the quality of grinding. in the range of 5… 20 °. It is noted that under 800 kg by loading the roller with the right location of the chopping knives, the lowest value of mathematical expectations of the distribution of crushed stem particles is set at 18.6 km / h. This value is 14%, 30%, 40% and 20% less than the speed , respectively, 7.45 km/h, 10.08, 13.6, 22 km/h. Exceedance of values of mathematical expectations of distributions of particles of stalks at a roller-shredder with the left scheme of an arrangement of knives over the right, for loading of 800 kg, at all speeds investigated is established. The lowest value of mathematical expectation for the right layout of the knives was set at a speed of 18.6 km / h, and for the left - at a speed of 13.6 km / h. The highest value of the mathematical expectation of the distribution of parts of sunflower stalks at the left location of the knives is set at a speed of 10.08 km/h, and for the right scheme - at a speed of 13.6 km/h. Exceeding the lowest value of mathematical expectation over the highest within one scheme of placement of knives was - on the left 48%, on the right 41%. In the roller with the left location of the cutting edge of the knives, with a load of 600 kg in the range of 51–100 mm, the percentage of crushed particles of sunflower stalks exceeded the corresponding values with a load of 800 kg. At speeds of 10.08 km/h, 13.6, 18.6 and 22 km/h, this excess was 1.9 times, 1.44, 1.96 and 1.99 times, respectively.
Research of Influence of the Scheme of an Arrangement of Knives of a Cat-shredder on Indicators of Quality of Crushing of Stalks of Sunflower
Keywords: подрібнення стебел соняшнику; рослинні рештки; коток-подрібнювач; показники якості подрібнення; shredding of sunflower stalks; plant remains; roller-shredder; indicators of grinding quality